Thermal-resistant lightweight concrete with polyethylene beads as coarse aggregates. (10th March 2018) - Ali, M.R.; Maslehuddin, M.; Shameem, M.; Barry, M.S.
Highlights: Polyethylene beads were utilized to develop thermal insulating lightweight concrete (TI-LWC). TI-LWC specimens were tested to assess their strength and thermal properties and durability. The unit weight, strength and durability were within the acceptable limits for LWC. The thermal resistance of the developed TI-LWC was very high indicating its usefulness in energy conservation. Abstract: There is an increasing trend towards developing thermal insulating lightweight concrete (TI-LWC) for structural applications. This is fueled by the desire to conserve energy and decrease greenhouse gas emission. Though few studies have been conducted to develop LWC, the thrust of the reported study was to develop TI-LWC. Polyethylene beads were utilized in the development of the reported TI-LWC. Trial mixtures were prepared utilizing polyethylene beads as a total or partial replacement of limestone coarse aggregates and the prepared specimens were tested to determine their unit weight and compressive strength. Mixtures showing low unit weight and acceptable compressive strength were selected for detailed evaluation, to determine mechanical properties, thermal resistance and durability. The unit weight of the developed mixtures was in the range of 1366–1744 kg/m 3 while the compressive strength was in the range of 17–27 MPa. The water absorption, depth of water penetration, and chloride ion permeability values were more than those of the normal weight concrete. However, the thermal resistance of the developed TI-LWCs, was very high indicating their usefulness in energy conservation.